2002
DOI: 10.1039/b111675d
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of Li+·Rg and Li+–Rg transport coefficients (Rg = He–Rn)

Abstract: High-quality [CCSD(T), large basis sets] ab initio potential energy curves are calculated for the series of Li + ÁRg species. These curves are employed to calculate spectroscopic parameters for these species, and are used to calculate transport properties for Li + moving through a bath of the relevant inert gas. The transport results obtained are statistically compared to previous ones. The present potentials appear to be the best available for Li + ÁAr, Li + ÁKr and Li + ÁXe and they rival the best ones for L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 38 publications
5
43
0
Order By: Relevance
“…Based on previous results [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and assuming that the present interaction potentials are accurate, we expect that the ion mobilities reported here are accurate to within about 0.2%. This is true both for the mobilities at fixed T 0 as a function of E / n 0 and for the zero-field mobilities as a function of T 0 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Based on previous results [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and assuming that the present interaction potentials are accurate, we expect that the ion mobilities reported here are accurate to within about 0.2%. This is true both for the mobilities at fixed T 0 as a function of E / n 0 and for the zero-field mobilities as a function of T 0 .…”
Section: Discussionsupporting
confidence: 69%
“…To date, we have studied 3 He + and 4 He + , 1 Cl − , 2 the alkali metal cations, [3][4][5][6] O − , 7 I − , 8 S − , 9 Hg + and Cd + , 10 O + , 11 F − , 12 Br − , 13 and Tl + . 14 Values calculated from our interaction potentials are in good to excellent agreement with experimental data where they exist, and in each case our potential was found either to be in agreement with the best potential available elsewhere or to be actually the best potential available.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] These are all closed-shell systems that serve as prototypes of cation/rare-gas interactions, as discussed in detail by Bellert and Breckenridge. 12 Very recently, we also tackled the more demanding open-shell system of O − with the three lightest rare gases, where it was shown 13 that it was important to employ potentials which took account of the spin-orbit interaction; this arises owing to the production of 2 ⌸ and 2 ⌺ + states upon interaction of the O − with the rare gas, and the interaction between the two ⍀ =1/2 states thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…The key to rational design of FAIMS separations is a priori calculation of K(E) for any ion/buffer gas pair. So far, this has been possible only when both the ion and buffer gases are monatomic, which creates an isotropic interaction potential that permits accurate scattering calculations [31,32]. For polyatomic ions, experiments have revealed that, in general, small ions including all monatomic species and nearly all small organic ions (including amino acids) belong to Type A, large and macromolecular ions such as proteins and polypeptides belong to Type C, and Type B is represented by relatively few intermediate-size species.…”
mentioning
confidence: 99%